2021
DOI: 10.3389/fphar.2021.734671
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation and Structural Transformation of Crassicauline A During Sand Frying Process and Antiarrhythmic Effects of its Transformed Products

Abstract: To ensure safety and efficacy, most Aconitum herbs should be processed before clinical application. The processing methods include boiling, steaming, and sand frying. Among these methods, the transformation pathways of diterpenoid alkaloids in the process of sand frying are more complicated. Therefore, crassicauline A, a natural product with two ester bonds, was chosen as the experimental object. Consequently, a known alkaloid, together with three new alkaloids, was derived from crassicauline A. Meanwhile, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Incarvine G (12), a novel monoterpene alkaloid isolated from Incarvillea sinensis Lam., is an ester composed of a monoterpene alkaloid with a cyclopentane[c]piperidine skeleton and glucose [19].…”
Section: Classes Of Terpenoidal Alkaloids 21 Monoterpenoid Alkaloidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Incarvine G (12), a novel monoterpene alkaloid isolated from Incarvillea sinensis Lam., is an ester composed of a monoterpene alkaloid with a cyclopentane[c]piperidine skeleton and glucose [19].…”
Section: Classes Of Terpenoidal Alkaloids 21 Monoterpenoid Alkaloidsmentioning
confidence: 99%
“…Incarvine G (12) showed cytotoxicity with the IC 50 value of 60.29 µM against MDA-MB-231 cells and inhibited the migration and invasion of breast cancer cells. Further mechanistic studies showed that Incarvine G inhibited the migration and invasion of MDA-MB-231 cells by inhibiting actin cytoskeleton formation [19].…”
Section: Antitumor Activitymentioning
confidence: 99%
See 1 more Smart Citation